2018
DOI: 10.1055/s-0038-1635111
|View full text |Cite
|
Sign up to set email alerts
|

Return to Sports after Unicompartmental Knee Arthroplasty: Reality or Utopia? A 48-Month Follow-Up Prospective Study

Abstract: Prospective case series, level 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(51 citation statements)
references
References 31 publications
3
47
0
1
Order By: Relevance
“…7 Previous studies have suggested a return-to-activity frequency as high as 88% for patients receiving a unicompartmental knee arthroplasty; however, the populations considered in these studies represent older populations returning to mostly low-impact activities. [27][28][29] In fact, a significant decrease of up to 88% was recognized for high-impact activities such as jogging and soccer in the study by Naal et al 27 Our study suggests that DFVO and MAT may offer an option to return to high-impact activities while prolonging the possible need for future knee arthroplasty.…”
Section: Discussionmentioning
confidence: 59%
“…7 Previous studies have suggested a return-to-activity frequency as high as 88% for patients receiving a unicompartmental knee arthroplasty; however, the populations considered in these studies represent older populations returning to mostly low-impact activities. [27][28][29] In fact, a significant decrease of up to 88% was recognized for high-impact activities such as jogging and soccer in the study by Naal et al 27 Our study suggests that DFVO and MAT may offer an option to return to high-impact activities while prolonging the possible need for future knee arthroplasty.…”
Section: Discussionmentioning
confidence: 59%
“…A systematic review and meta-analysis regarding RTS in elderly patients after UKA showed that higher return rates were observed for low-impact sports, whereas high-impact sports prevented a full return to activities [ 25 ]. Since there are risks of femoral component loosening and polyethylene wear in UKA [ 26 28 ], RTS after both surgical procedures needs to be assessed by long-term follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review and meta-analysis regarding RTS in elderly patients after UKA showed that higher return rates were observed for low-impact sports, whereas high-impact sports prevented a full return to activities [20]. Since there are risks of femoral component loosening and polyethylene wear in UKA [21][22][23], RTS after both surgical procedures needs to be assessed by long-term follow-up.…”
Section: Discussionmentioning
confidence: 99%